Analysis of Metacognitive Ability in Mathematics Problem Solving of SMA Students at Ngemplak Boyolali - Safitri, Meilani; Suryani, Nunuk (Journal of Mathematics and Mathematics Education, 2022)
Metacognitive ability is closely related to problem solving ability. This research is a survey research involving 150 students of class X from four high schools in Ngemplak Boyolali. The purpose of this study is to describe the results of the analysis of metacognitive abilities in solving mathematical problems. Data was collected using a Metacognitive Awareness Inventory (MAI) questionnaire. Data analysis was carried out quantitatively and qualitatively. The results showed that 23% of students had high metacognitive abilities, 20% of students had moderate metacognitive abilities, and 57% of students had low metacognitive abilities. Most students who have high metacognitive abilities are able to use their metacognitive abilities in solving mathematical problems. Almost all students who have low metacognitive abilities do not use their metacognitive abilities in solving mathematical problems. Overall, students are less than optimal in using metacognitive abilities when solving mathematical problems.